INNOVATIVE PRACTICES FOR IMPLEMENTING INCLUSION IN HIGHER EDUCATION INSTITUTION - Iurii, Gutsul; Blavt, Oksana (European Science, 2025)
The paper examines the issue of implementing inclusive educational practices in higher education. As a tool for implementing inclusion, the main pedagogical aspects of inclusive physical education of students are identified, as well as the possibilities f